ChemInform Abstract: Continuous Flow Reactions in Water for the Synthesis of Propargylamines via a Metal‐Free Decarboxylative Coupling Reaction. Issue 46 (November 2015) - Jung, Bongkyun; Park, Kyungho; Song, Kwang Ho; Lee, Sunwoo
Abstract Alkynyl carboxylic acids undergo decarboxylative coupling with amines and paraformaldehyde, using a continuous flow reaction system to give propargylamines in excellent yields.